2008
DOI: 10.1007/s11270-008-9803-z
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Bioaccumulation of Organochlorine Compounds in Fish and their Selective Biotransformation in Top Predators from Lake Maggiore (Italy)

Abstract: Fish and piscivorous bird eggs collected in 2003 from Lake Maggiore (Italy), were analysed for PCB and DDT contamination. Lake Maggiore has been severely polluted by DDT through production of the pesticide within its catchment. Although agricultural application of DDT was banned in Italy in the 1978, industrial production continued until 1996, with enough contamination of water and soil for serious bioaccumulation in the lake biota. PCB and DDT concentrations in a whitefish (Coregonus macrophthalmus Nusslin 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 54 publications
1
21
0
3
Order By: Relevance
“…Ambrosetti and colleagues (2006) have shown an increase of short and very intense rain 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 events coupled with long drought periods, and increased pollutant loads from the catchment (Galassi et al, 2006;Volta et al, 2009;Guilizzoni et al, 2012), due to changes in hydrology and precipitation regimes, have been also identified. Furthermore, an increase in the duration of the thermal stratification and stability of the water column was observed, probably triggering cyanobacteria blooms (Morabito, 2007).…”
Section: Lake Maggiore: Reduction In Cold Water Species and Increase mentioning
confidence: 99%
“…Ambrosetti and colleagues (2006) have shown an increase of short and very intense rain 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 events coupled with long drought periods, and increased pollutant loads from the catchment (Galassi et al, 2006;Volta et al, 2009;Guilizzoni et al, 2012), due to changes in hydrology and precipitation regimes, have been also identified. Furthermore, an increase in the duration of the thermal stratification and stability of the water column was observed, probably triggering cyanobacteria blooms (Morabito, 2007).…”
Section: Lake Maggiore: Reduction In Cold Water Species and Increase mentioning
confidence: 99%
“…During the last 50 years, Italian lakes have been heavily affected by anthropogenic pressures such as organic (Mosello & Giussani 1997) and chemical pollution (Galassi et al 1981;Volta et al 2008) but also by erroneous fish management and stocking practices often characterized by the introduction of alien species. After the 1950s the presence of exotic species in Italy increased rapidly and the adverse effect of these invaders is now a major problem for the local fish fauna (Bianco 1998;Bianco & Ketmeier 2001;Gherardi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…According to the available literature, the presence of residues of some persistent organic pollutants in tissues of freshwater fish is still found in many countries [3,6,[9][10][11][12]. The problem with DDT and PCB contamination of food and environment in the areas of their former manufacture still occurs.…”
Section: Resultsmentioning
confidence: 99%
“…The bioaccumulation of contaminants such as DDTs (mainly as DDE), PCBs, dioxins, and heavy metals by fish represents a potentially significant risk to piscivorous wildlife [11,12,17]. Fish often comprise a substantial dietary portion of mammalian and avian species, and therefore represent a significant route of contaminant exposure.…”
Section: Resultsmentioning
confidence: 99%